Olanzapine-induced lipid disturbances: A potential mechanism through the gut microbiota-brain axis - Zhu, Zhenyu; Gu, Yuxiu; Zeng, Cuirong; Yang, Man; Yu, Hao; Chen, Hui; Zhang, Bikui; Cai, Hualin (Frontiers in Pharmacology, 2022)
Objective: Long-term use of olanzapine can induce various side effects such as lipid metabolic disorders, but the mechanism remains to be elucidated. The gut microbiota-brain axis plays an important role in lipid metabolism, and may be related to the metabolic side effects of olanzapine. Therefore, we explored the mechanism by which olanzapine-induced lipid disturbances through the gut microbiota-brain axis. Methods: Sprague Dawley rats were randomly divided into two groups, which underwent subphrenic vagotomy and sham surgery. Then the two groups were further randomly divided into two subgroups, one was administered olanzapine (10 mg/kg/day) by intragastric administration, and the other was administered normal saline by intragastric administration (4 mL/kg/day) for two weeks. The final changes in lipid parameters, gut microbes and their metabolites, and orexin-related neuropeptides in the hypothalamus were investigated among the different groups. Results：Olanzapine induced lipid disturbances as indicated by increased weight gain, elevated ratio of white adipose tissue to brown adipose tissue, as well as increased triglyceride and total cholesterol. Olanzapine also increased the Firmicutes/ Bacteroides (F/B) ratio in the gut, which was even aggravated by subphrenic vagotomy. In addition, olanzapine reduced the abundance of short-chain fatty acids (SCFAs) metabolism related microbiome and 5-hydroxytryptamine (5-HT) levels in the rat cecum, and increased the gene and protein expression of the appetite-related neuropeptide Y/agouti-related peptide (NPY/AgRP) in the hypothalamus. Conclusion: The abnormal lipid metabolism caused by olanzapine may be closely related to the vagus nerve-mediated gut microbiota-brain axis.